Unguarded Moments. Spectral spaces of the unsuspecting mind - Ryden, Anne (2018)
Marcel Proust’s meditation as he picked over the crumbs of a long-eaten madeleine biscuit has inspired and informed several areas of inquiry into (the uncertain science of) memory and recall. The Proust-effect, defined by Cretien van Campen (2014) as ‘an involuntary, sensory-induced, vivid and emotional reliving of events from the past’ goes some way towards illustrating the experience of having a memory triggered by something ordinary. But where Proust’s experiences all progress from a brief awakening though a slow unfolding of recollections to a full-blown memory, the experience that interests me is less gentle and a lot more immediate.